Biological and Optimal Control Model for Powdery Mildew Disease in Mango Plants and Fruits - K. Vaishnavi; R. Malinidevi (Applications of Modelling and Simulation)
Powdery mildew is a major threat to mango plants, leading to significant agricultural and financial losses. This study introduces innovative mathematical models to capture the dynamics of powdery mildew infection in mango fruits and proposes an optimal control strategy to minimize disease spread and treatment costs. By applying advanced asymptotic techniques, such as the New Homotopy Perturbation Method, Adomian Decomposition Method, and Variational Iteration Method, this research derives novel approximate analytical solutions, which are rigorously validated against numerical results. The developed models offer a robust framework for understanding the disease dynamics and optimizing biological control measures, with a focus on minimizing both disease transmission and treatment expenses. The results demonstrate the efficacy and accuracy of these approaches, providing valuable insights into pest management strategies in mango cultivation.